Plasma IGFBP-3 and IGFBP-5 levels are decreased during acute manic episodes in bipolar disorder patients - Fernández-Pereira, Carlos; Penedo, Maria Aránzazu; Alonso-Núñez, Adrián; Rivera-Baltanás, Tania; Viéitez, Irene; Prieto-González, José María; Vilariño-Vilariño, María Isabel; Olivares, José Manuel; Ortolano, Saida; Agís-Balboa, Roberto Carlos (Frontiers in Pharmacology, 2024)
Bipolar disorder (BD) is a recurrent and disabling psychiatry disorder, related to low-grade peripheral inflammation and altered levels of members of the insulin-like growth factor (IGF). The aim of this study was to evaluate plasma levels of IGF-2, IGFBP-1, IGFBP-3, IGFBP-5, IGFBP-7 and inflammatory markers such as tumor necrosis factor α (TNF-α), Monocyte chemoattractant protein 1 (MCP-1) and Macrophage inflammatory protein 1 β (MIP-1β). We used the Young Mania Rating Score (YMRS) to determine the severity of the symptomatology, while proteins were measured by enzymelinked immunosorbent assay (ELISA). We included 20 patients with BD that suffered from a manic episode and 20 controls. Some BD patients (n = 10) were evaluated after a period (17 ± 8 days) of pharmacological treatment. No statistical difference was found in IGF-2, IGFBP-1, IGFBP-7, TNF-α and MIP-1β. However, IGFBP-3 and IGFBP-5 were found statistically decreased in BD patients. Conversely, MCP-1 was significantly increased in BD but their levels were normalized after treatment. Intriguingly, only IGFBP-1 levels were significantly decreased after treatment. No significant correlation was found between YMRS and any of the proteins studied either before or after treatment, nor between IGF proteins and inflammatory markers. To some extent, IGFBP-3 and IGFBP-5 might be further explored as potential indicators of treatment responsiveness or diagnosis biomarkers in BD.